Promoting equity and justice: harnessing the right to food for Africa's food security - Helen Onyeaka; Kehinde Favour Siyanbola; Adenike A. Akinsemolu; Phemelo Tamasiga; Ifeoma Elizabeth Mbaeyi-Nwaoha; Clinton Emeka Okonkwo; Olumide A. Odeyemi; Elijah Kolawole Oladipo (Agriculture & Food Security)
Abstract This paper examines the state of food security in African nations within the context of promoting equity and justice through the right to food. It discusses the various challenges faced by the African nations, including poverty, climate change, and urbanization, which impact the availability, accessibility, and utilization of food resources. It further emphasises the importance of secure land tenure rights, gender equality and women empowerment, good nutrition and safe food, sustainable agricultural practices as well as sustainable food system transformation to ensure food and nutrition security, environmental quality and human well-being. This paper further advocates for stringent efforts involving governance, accountability, and international cooperation to achieve sustainable development goals and ensure food security for all in Africa, thereby fostering equity and justice in the food system.